2010
DOI: 10.1185/03007995.2010.505126
|View full text |Cite
|
Sign up to set email alerts
|

Fatality rates in published reports of RSV hospitalizations among high-risk and otherwise healthy children

Abstract: Children at high risk for RSV (CLD, CHD and prematurity), those with severe underlying comorbidities, or those with nosocomial RSV appear to be at increased risk for death after RSV hospitalization. More data are needed on cause of death and how much is directly attributable to RSV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
88
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 46 publications
7
88
0
6
Order By: Relevance
“…Gerson and colleagues demonstrated that the ovine airway secretions contain LPO and that a reduction of LPO function by dapsone administration reduces antibacterial activity (23), thus demonstrating that the ovine airway has a functional LPO-dependent antibacterial system. The present study further demonstrates that the ovine ASL contains SCN 2 and for the first time shows that intravenous or intragastric delivery of I 2 increases ovine ASL [I 2 ]. The results also suggest that the upper airway of lambs recapitulates the halide-transporting activity of the human nasal mucosa.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Gerson and colleagues demonstrated that the ovine airway secretions contain LPO and that a reduction of LPO function by dapsone administration reduces antibacterial activity (23), thus demonstrating that the ovine airway has a functional LPO-dependent antibacterial system. The present study further demonstrates that the ovine ASL contains SCN 2 and for the first time shows that intravenous or intragastric delivery of I 2 increases ovine ASL [I 2 ]. The results also suggest that the upper airway of lambs recapitulates the halide-transporting activity of the human nasal mucosa.…”
Section: Discussionmentioning
confidence: 94%
“…In industrialized countries, human RSV (hRSV) accounts for up to 70% of hospitalized bronchiolitis cases (1)(2)(3). Although the antiviral drugs palivizumab and ribavirin have virucidal activity against RSV in vivo, there are no fully satisfactory therapeutic regimens or vaccines (4)(5)(6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Risk of RSV-bronchiolitis development with severe respiratory failure phenomena requiring massive infusion and inhalation therapy and even artificial lung ventilation (ALV) [14] is the highest in these children. According to different data, RSVI mortality in children with BPD and CHD is 2-37%; in children born before the 36 th gestation week -0-6.1% [15]; the variation is caused by the level of economy and public health development in the country. According to the analysis of 36 epidemiologic trials, RSVI mortality in the developing countries reaches 5.3-6.2%, in the developed countries -0.3-0.5% [4].…”
Section: Short-term Rsv-infection Effects: Morbidity and Mortalitymentioning
confidence: 99%
“…It is widely known that RSV is highly contagious and often causes outbreaks of acute respiratory diseases and lower respiratory tract infections at resuscitation units, neonatal pathology units, children's collectives and retirement homes. The rate of fatal outcomes among children in the event of nosocomial RSV infection outburst may be as high as 12% [33]. The epidemic situation concerning RSV required development of efficient preventative measures.…”
mentioning
confidence: 99%